The effects of indoor air quality on health and productivity of workers in a manufacturing industry in Malaysia - Khairul Iman, S.; Nurud Suria, Suhaimi (Penerbit Universiti Malaysia Pahang, 2023)
Indoor Air Quality (IAQ) has a significant impact on health and quality of life in general. IAQ can be affected by various chemicals, including gases (i.e., carbon monoxide, ozone, radon), volatile organic compounds, particulate matter and fibres, organic and inorganic contaminants, and biological particles such as bacteria, fungi, and pollen. Studies of buildings have indicated that poor IAQ can cause health problems, affect occupants’ productivity. This research analyses how the indoor air quality can affect the health and productivity of workers in a manufacturing industry in Malaysia. As for the health effects, poor indoor air quality can give short-term effects as well as to a long-term risk. To complete this study, a set of questionnaires were distributed to 50 workers in the manufacturing industry in Malaysia. The findings indicated a modest positive correlation between IAQ and worker health, while significant correlation was observed between IAQ and productivity. In conclusion, there are many actions and recommendations that can be contemplated in protract the best and excellent reputation and performance of the company moreover by considering improving the indoor air quality, health and productivity of workers.